America’s Most Successful Export to Japan: Continuous Improvement Programs - and Dean M., Schroeder; Robinson, Alan G. (MIT Sloan Management Review, 1991)
CONTINUOUS IMPROVEMENT Programs (CIPs) unleash employee experience and I creativity to improve both products and processes. They are often cited as the most important difference between the Japanese and Western management styles and as a major factor in Japan’s economic success.2Yet the CIP was conceived, developed, and brought to maturation in the United States. After World War II, the U.S. government helped to export it to Japan, where it was well received and promptly flourished. Despite the long history and well-documented benefits of such systems, few U.S. companies have invested effort in CIPs equivalent to that of their Japanese competitors. Japanese companies have put almost forty years into the development and refinement of CIPs, or kaizen programs as they are known in Japan, and have brought the art and science of managing them to new levels of sophistication. The aim of these programs is precisely to design and implement a system whose natural equilibrium is constant improvement and change. How can a company that does not have such a program compete with one that does? In this paper we give the historical background of CIPs, which we believe is essential for a useful understanding of these programs. We document their export across the Pacific immediately following World War II and illustrate their power as a competitive weapon when fully and properly deployed. We then identify and discuss requirements for successful implementation and suggest reasons why many U.S. firms find them difficult to start and maintain. We conclude by arguing that what is commonly perceived to be the “best practice” of CIP management is itself open to improvement. Throughout the article, we identify promising directions for companies to pursue so that all minds in the company, not just those of a few at the top, are actively solving problems, reducing costs, and eliminating waste.